Effect of Water-Cement Ratio and Liquidity Index on the Deep Mixing Method using Cement Slurry: A Case Study of Kaolin Clay Powder - SOME, Donzala David; USUI, Hirofumi; MITSUSE, Kimihiro; SINDETE, Mathiro Jose; PASTOR, Jose Luis; HINO, Takenori (Lowland Technology International, 2024)
The liquidity index is a crucial factor in geotechnical engineering used to assess soil behavior under varying loading conditions. It provides valuable information about a soil's deformability when subjected to loads, which is vital for structural and foundation design. In the domain of soil-cement, especially within the deep mixing method (DMM), various factors influence the strength of cement-stabilized soft soils. These factors include water content, cement content, water-cement ratio (W/C), and soil consistency. Notably, a lower W/C ratio tends to result in higher unconfined compressive strength (). In the case of the Saga lowland, where soft cohesive soil with high compressibility and low strength is prevalent, the standard practice employs a W/C ratio of 1.0 with a cement content of 110 kg/m³ for most projects. However, this research introduces an innovative approach: utilizing a W/C ratio of 1.5 with the same cement content of 110 kg/m³, through laboratory experiments. It investigates the effects of the Liquidity Index (IL), instead of soil sensitivity, and the water-cement ratio on the unconfined compressive strength of specimens prepared using commercial kaolin clay powder. These specimens are prepared with varying initial water content (), determined based on the liquid limit value (), to achieve different soil states. As a result, there is a slight reduction in strength, but it is more uniformly distributed. This approach is designed to bolster support for the existing infrastructure in the Saga lowland. The significance of this study in the field of DMM lies in advocating for an increased W/C ratio to ensure not only the quality of the mixture but, more importantly, the uniformity of strength within the columns. In this context, the optimal ratio depends on a soil candidate consistency parameter, such as its IL.